Urgensi Intelektualitas dan Kreativitas dalam Membuat Konten Digital di Era Society 5.0 Perspektif Gender - Wahyu Pratama; Aji Wibawa (Universitas Ngeri Malang, 2022)
Digital content has become a distinct trend in the midst of technological advances, especially in the era of society 5.0 with the latest inventions such as artificial intelligence. Creating digital content usually requires qualified intellect and creativity. In this context, gender may also have an influence on the level of intellectuality and creativity of each individual. The research was carried out using descriptive qualitative methods and literature studies seeking information from various literatures. The results obtained are an understanding of the relationship between intellect and creativity with digital content, the relationship between these 3 things will be studied from various literature. This point will discuss whether intellect and creativity have an influence on the quality of digital content produced. In the next point there is a discussion about how big the relationship between gender is with intellect and creativity. This question departs from the assumption that there are differences in the mindset of each gender. The last point is the development of digital content in the era of society 5.0. In the end, the results of the discussion obtained at this point will focus on how humans adapt in the midst of the growing development of artificial intelligence. It is feared that intelligence that is increasingly developing can replace humans, especially in terms of creating digital content. Konten digital menjadi tren tersendiri di tengah kemajuan teknologi, terutama di era society 5.0 dengan adanya penemuan mutakhir seperti kecerdasan buatan. Dalam pembuatan konten digital biasanya memerlukan intelektualitas dan kreativitas yang mumpuni. Dalam konteks ini gender mungkin saja juga memberikan pengaruh terhadap tingkat intelektualitas dan kreativitas setiap individu. Penelitian dilakukan dengan metode deskriptif kualitatif dan studi kepustakaan yang mencari informasi dari berbagai literatur. Hasil yang diperoleh adalah pemahaman tentang kaitan intelektualitas dan kreativitas dengan konten digital, keterkaitan 3 hal tersebut akan dikaji dari berbagai literatur. Poin ini akan membahas tentang apakah intelektualitas dan kreativitas memberikan pengaruh pada kualitas konten digital yang dihasilkan. Pada poin selanjutnya ada pembahasan tentang seberapa besar hubungan gender dengan intelektualitas dan kreativitas. Pertanyaan ini berangkat dari asumsi adanya perbedaan pola pikir setiap gender. Poin terakhir adalah perkembangan konten digital di era society 5.0. Pada akhirnya hasil pembahasan yang diperoleh pada poin ini akan berfokus pada bagaimana cara manusia beradaptasi di tengah perkembangan kecerdasan buatan yang kian berkembang. Kecerdasan yang semakin berkembang dikhawatirkan dapat menggantikan manusia khususnya dalam hal pembuatan konten digital.